Manifestes en performance : de quelques manifestes de poésie expérimentale - Gaëlle Théval (Itinéraires)
Our study focuses on three manifestos, produced between 1961 and 1978 by three central figures in the field, Pierre Garnier, Bernard Heidsieck and Julien Blaine, which appear as milestones for mapping the field and history of experimental poetry in France. We are interested to the critical and programmatic contents as much as to the modes of action of these manifestos: indeed, the manifesto can not be reduced to a literary genre but is “a gesture, an act” “primarily a pragmatics of discourse, a sociological reading, an analysis in terms of intervention strategies in the field of the institution” (Gleize 1980: 12). What about the act of demonstration in experimental poetry and especially in “action poetry”? Our purpose is articulated around three actions: to quit the book, to make a group exist, and to put poetry in action.